The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/ico.0000000000000457
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Diagnosis of Limbal Stem Cell Deficiency

Abstract: Clinical examination can lead to misdiagnosis of LSCD. Immunocytochemical detection of K7/K13 on corneal ECs collected by IC is reproducible, noninvasive, and highly effective in this indication, but without any quantification of the degree of the disease. This time-consuming technique requires skilled technicians and laboratory facilities, reserving it for planned limbal reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…It seems a good approach to distinguish the limbus from the conjunctiva based on goblet cells, which were used to diagnose LSCD [ 109 ]. Controversially, the Stevens–Johnsons syndrome and long-term administration of glaucoma drugs could lead to LSCD with no goblet cells invasion [ 110 ]. Some investigators reported that CK19, CK13 and MUC5AC can serve as biomarkers of conjunctival epithelial cells [ 110 , 111 ], but others argued that the expression of CK19 was detected both on the limbal and CECs [ 27 ].…”
Section: Difficulties In the Study Of Lsc-specific Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems a good approach to distinguish the limbus from the conjunctiva based on goblet cells, which were used to diagnose LSCD [ 109 ]. Controversially, the Stevens–Johnsons syndrome and long-term administration of glaucoma drugs could lead to LSCD with no goblet cells invasion [ 110 ]. Some investigators reported that CK19, CK13 and MUC5AC can serve as biomarkers of conjunctival epithelial cells [ 110 , 111 ], but others argued that the expression of CK19 was detected both on the limbal and CECs [ 27 ].…”
Section: Difficulties In the Study Of Lsc-specific Biomarkersmentioning
confidence: 99%
“…Controversially, the Stevens–Johnsons syndrome and long-term administration of glaucoma drugs could lead to LSCD with no goblet cells invasion [ 110 ]. Some investigators reported that CK19, CK13 and MUC5AC can serve as biomarkers of conjunctival epithelial cells [ 110 , 111 ], but others argued that the expression of CK19 was detected both on the limbal and CECs [ 27 ]. Although Ramirez-Miranda et al believed that CK13 was more specific than CK19 in terms of identification of conjunctival epithelial cells [ 92 ], Poli et al showed that CK13 was expressed in both the conjunctival epithelium and the suprabasal and superficial layers of the limbal epithelium [ 110 ].…”
Section: Difficulties In the Study Of Lsc-specific Biomarkersmentioning
confidence: 99%
“…Severe damage to the limbal epithelial cells from various etiologies in the limbal region may lead to loss of the limbal epithelial cells [ 2 ], so called limbal stem cell deficiency (LSCD). LSCD, manifested by chronic inflammation, neovascularization, and goblet cell invasion into the cornea, may be complicated by persistent corneal epithelial defects, ulceration, and even perforation of the cornea [ 3 , 4 ]. The cornea may ultimately be healed by fibrosis, however, the vision will be greatly impaired.…”
Section: Introductionmentioning
confidence: 99%
“…159 The directed differentiation of iPSCs into CECs depends on the expression of cytokeratins (CK) 12 and 13, while CK3 expression was evident in the cell lines derived from the CE. 160,161 To improve the yields of mature CECs and to obtain a stratified cell sheet resembling the native CE, a consistent and efficient stratification method has to be employed. It is not uncommon to detect variation in the differentiation potential among different hiPSC lines, with donor identity and gender being among the potential sources of variation in the case of hiPSC lines.…”
Section: Induced Pluripotent Stem Cells (Ips)mentioning
confidence: 99%